1984
DOI: 10.1111/j.1442-9993.1984.tb01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Status of coastal dune communities invaded by Chrysanthemoides monilifera

Abstract: It has often been assumed that the introduced species Chrysanthemoides monilifera is displacing native species in invaded coastal communities in Australia but no direct evidence has been presented that this displacement is occurring and. if so. to what extent. At an invaded site near Moruva. New South Wales, we found strong negative correlations between the presence (measured as cover, frequency or volume of shrub) of C. monilifera and Acacia longifolia, the hitherto dominant native species, and ofC. monilifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 1 publication
3
46
0
Order By: Relevance
“…In previous studies we have shown that the hydrophobic extracts (dichloromethane and acetone soluble) of bitou bush roots, leaves and soil, consistently inhibited the germination and seedling growth of a range of native plants (Ens unpublished data), including the native dominant of the system, acacia (Austin 1978;Weiss and Noble 1984b). This study was designed to identify the hydrophobic compounds that were likely to be responsible for the observed inhibition of seedling growth by the crude hydrophobic root and soil extracts.…”
Section: Introductionmentioning
confidence: 97%
“…In previous studies we have shown that the hydrophobic extracts (dichloromethane and acetone soluble) of bitou bush roots, leaves and soil, consistently inhibited the germination and seedling growth of a range of native plants (Ens unpublished data), including the native dominant of the system, acacia (Austin 1978;Weiss and Noble 1984b). This study was designed to identify the hydrophobic compounds that were likely to be responsible for the observed inhibition of seedling growth by the crude hydrophobic root and soil extracts.…”
Section: Introductionmentioning
confidence: 97%
“…High density of neighbours may reduce plant height (Harper 1977), and time of owering may be changed (The baud et al 1996). Studies have produced strong or highly suggestive evidence that the competitiveness of established invaders is correlated with their distribution (Weiss and Noble 1984). Competitive interactions between native and introduced species may thus aect both plant performance and population dynamics.…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that exotics often differ from native species in ways that potentially contribute to their success within introduced habitats (e.g. Weiss and Noble, 1984;Busch and Smith, 1995;Dukes and Mooney, 1999;Yamashita et al, 2000;Horton et al, 2001). The objective of this study was to determine if gas exchange responses of Schinus were significantly different from native species in two communities, a native rock pineland community and a disturbed previously farmed area.…”
Section: Introductionmentioning
confidence: 99%